2022
DOI: 10.1371/journal.pone.0265941
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support on postpartum mental health:  An instrumental variable analysis

Abstract: The postpartum period is a challenging transition period with almost one in ten mothers experiencing depression after childbirth. Perceived social support is associated with mental health. Yet empirical evidence regarding the causal effects of social support on postpartum mental health remains scarce. In this paper, we used a nationally representative panel data of women to examine causality between perceived social support and postpartum mental health. We used fixed-effect method and included dependent variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
2
10
0
2
Order By: Relevance
“…The current study also found that adult mothers with medium social support had 51% lower odds of experiencing PPD compared to women with low social support. Similar findings were also observed in previous studies (Cho et al, 2022;Inekwe & Lee, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study also found that adult mothers with medium social support had 51% lower odds of experiencing PPD compared to women with low social support. Similar findings were also observed in previous studies (Cho et al, 2022;Inekwe & Lee, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The current study also found that adult mothers with medium social support had 51% lower odds of experiencing PPD compared to women with low social support. Similar findings were also observed in previous studies (Cho et al, 2022; Inekwe & Lee, 2022). Furthermore, the provision of intensive and professional support such as home visits, telephone support, and interpersonal psychotherapy during the postpartum period is effective in reducing PPD (Dennis & Dowswell, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…63 In the postpartum period, maternal social support is also known to serve as a protective factor for maternal mental health. 64,65 In their study, Hatch, Swerbenski, and Gray 33 observed that the association between maternal ACEs and children’s behavioural problems postnatally was conditional on the level of maternal social support, where moderate to high levels buffered the negative impacts of maternal ACEs on children’s behaviour. Therefore, not only may social support act as a protective factor for maternal mental health, it can also prevent the intergenerational transmission of poor behavioural outcomes to children.…”
Section: Discussionmentioning
confidence: 99%
“…The themes identified within this review are consistent with other literature exploring perinatal mental health. Social support is identified in several studies exploring perinatal mental health distress in general populations and is found to be protective, reducing the impact of stress during pregnancy, and mitigating the impact of stress during the postnatal period (Lavender et al 2016;Inekwe & Lee 2022;Shorey et al 2015;Li et al 2021). Perinatal interventions that strengthen social support are therefore recommended for both preventing and treating mental health distress.…”
Section: Characteristics Of Approaches and The Cultural Continuummentioning
confidence: 99%